PROGRAM KINERJA HUMAS TERHADAP PENINGKATAN DAYA TARIK DAN PENCAPAIAN TARGET PPDB - Silva Az-Zahra; Shelly Shelly; Ghea Nur Azizah; Abelia Sri Maharani (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the performance of public relations (PR) programs in increasing school attractiveness and achieving New Student Admission (PPDB) targets at MTs Islamiyah Kedaung through communication strategies, collaboration, and the use of social media. This study employed a qualitative descriptive approach with field research methods. Data were collected through observation, in-depth interviews, and documentation involving teachers, students, school committees, and the community as key informants. The findings indicated that the school’s PR implemented integrated strategies through socio-cultural-based promotion involving community leaders, consistent publication of school activities, and optimizing social media for branding. Additionally, internal-external collaboration, scholarship programs, extracurricular activities, and a reputable service quality were key factors in strengthening community interest. Challenges such as resource constraints and inter-institutional competition were addressed through collective coordination and continuous evaluation. This research provides an integration model between traditional socio-cultural promotion strategies and media digitalization as an effective solution for private schools in facing competitive admission processes. The contribution of public relations proved to be collectively significant in enhancing the institutional image and maintaining the stability of new student enrollment.